"It's a unique role!" Perspectives on tutor attributes and expertise in distance language teaching - Shelley, Monica; White, Cynthia; Baumann, Uwe; Murphy, Linda (International Review of Research in Open and Distributed Learning, 2006)
This article outlines the background to, and progress on, a project based on work carried out at the Open University UK (OUUK). The aim of the project is to articulate the attributes and expertise required by tutors of languages in distance education. A review of the literature on the roles and competencies required for tutors operating at a distance indicates that the specific context of language teaching has received relatively little attention from researchers in the field. There has, however, been considerable interest in the skills and attributes necessary for face-to-face language teaching in the classroom, which is outlined here. Issues of definition and research perspective are discussed, as well as the advantages and disadvantages of various research approaches. The different stages and outcomes of the collaborative project are described in detail, demonstrating how the unfolding research design allowed opportunities for consultation, reflection, and responsive changes. The next stages of consultation are outlined, together with implications for the on-going professional development of tutors.